MANAJEMEN KEUANGAN BERBASIS AJARAN HINDU DALAM MENCAPAI SUSTAINABILITAS BISNIS - I Nyoman Bontot; Ahmad Subagyo; Martino Wibowo; Anas Iswanto Anwar (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
This study explores the integration of Hindu ethical principles into the financial governance of Village Credit Institutions (LPDs) in Bali and its contribution to institutional sustainability. Employing a mixed-method approach, the research combines hermeneutic interpretation of sacred Hindu scriptures-Rgveda, Yajurveda, Atharvaveda, Bhagawad Gita, Sarasamuccaya, Manusmrti, and Arthasastra-with quantitative analysis of financial performance across 1.308 LPDs in nine regencies. Four core principles-Karma (ethical productivity), Dharma (social responsibility), Kama (motivational fulfillment), and Artha (material prosperity)-are operationalized within a holistic model of Hindu-based financial management. Empirical testing confirms are positive relationship between these principles and financial indicators such as profit margin, return on assets, and capital growth. The findings demonstrate that Hindu-based financial governance enhances accountability, strengthens community trust, improves leadership integrity, and promotes long-term business sustainability. This study provides a culturally grounded and ethically robust framework for developing resilient and inclusive community-based microfinance institutions in plural financial systems.